1994
DOI: 10.1128/jvi.68.10.6824-6828.1994
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel binding site for the human immunodeficiency virus type 1 envelope protein gp120 on human fetal astrocytes

Abstract: 1251_labeled recombinant gpl20 bound to primary cultures of human fetal astrocytes with a single class of 260-kDa binding sites, with a Kd of 26 nM and maximal number of binding sites of 29.9 fmol/4 x 104 cells. Neither CD4 nor galactocerebroside was detectable on astrocytes, and 2-51-labeled recombinant gpl20 binding to astrocytes was not blocked by antibodies against galactocerebroside or the gpl20 binding domain of CD4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(14 citation statements)
references
References 34 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…Studies with in situ polymerase chain reaction and laser capture dissection microscopy have confirmed that productive infection occurs exclusively within perivascular macrophages,113 and to a lesser extent in microglia, with restrictive or nonproductive infection of astrocytes 114, 115. Because CD4 is not present on astrocytes, this infection must be CD4 independent 116, 117. Neurons are not infected in humans, and regionally, most productive HIV infection is seen within the basal ganglia, brainstem, and deep white matter 118, 119.…”
Section: Diagnostic Studies In Handsmentioning
confidence: 99%
“…Studies with in situ polymerase chain reaction and laser capture dissection microscopy have confirmed that productive infection occurs exclusively within perivascular macrophages,113 and to a lesser extent in microglia, with restrictive or nonproductive infection of astrocytes 114, 115. Because CD4 is not present on astrocytes, this infection must be CD4 independent 116, 117. Neurons are not infected in humans, and regionally, most productive HIV infection is seen within the basal ganglia, brainstem, and deep white matter 118, 119.…”
Section: Diagnostic Studies In Handsmentioning
confidence: 99%
“…These activated macrophages appear to secrete arachidonic acid, which perturbs the highaffinity excitatory amino acid uptake system of astrocytes. Nonetheless, it is likely that gp120 manifests additional actions, which may include direct effects on astrocytes, as recent reports have suggested (Ma et al, 1994;Codazzi et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Human fetal brain tissue (gestational age, 13 to 16 weeks) was obtained with written consent from women undergoing elective termination of preg-nancy and with approval of the University of Manitoba Human Ethics Committee. Human fetal astrocyte and neuron cultures were prepared as described previously (19,20). Purity of astrocytes (Ͼ95%) and neurons (Ͼ70%) was determined by immunostaining for glial fibrillary acidic protein and microtubule-associated protein 2, respectively.…”
mentioning
confidence: 99%